Fragmented Indicators in Local Stunting Governance Across Pasuruan Villages, East Java - Wahyu Intan Lestari; Aminullah Aminullah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Stunting reduction in Indonesia is formally designed as an integrated policy agenda involving health services, village governance, family assistance, community organizations, and households. However, integrated policy design does not necessarily lead to integrated local implementation. This study examines how indicator fragmentation shapes stunting policy implementation across four villages in Pasuruan, East Java. Using a comparative qualitative case study design, data were collected through semi structured interviews with 52 informants, document analysis, and field observation. The findings show that implementation became fragmented when village governments, Puskesmas, Posyandu cadres, family assistance teams, district agencies, and households operated under different targets, datasets, reporting routines, and accountability demands. Coordination often remained procedural, emphasizing meetings, reports, and activity completion rather than substantive household follow up. Posyandu cadres played a critical bridging role between policy systems and households, but faced administrative burdens, limited incentives, and weak authority in formal decision making. The study contributes conceptually by developing indicator fragmentation as an analytical lens for explaining why integrated public health policy becomes fragmented in local practice. Practically, it highlights the need to align indicators, data, budgeting, service delivery, and household follow up in village level stunting governance.